Environmental exposures and child and maternal gut microbiota in rural Malawi - Kortekangas, Emma; Kamng'ona, Arox W.; Fan, Yue‐Mei; Cheung, Yin Bun; Ashorn, Ulla; Matchado, Andrew; Poelman, Basho; Maleta, Kenneth; Dewey, Kathryn G.; Ashorn, Per (Paediatric and perinatal epidemiology, 2020)
Background Gut microbiota composition is associated with child health, but the effect of the environment on microbiota composition is not well understood. Few studies have been conducted in low‐income settings where childhood malnutrition is common and possibly related to microbiota composition. Objectives To investigate whether gut microbiota composition in young children and their mothers is associated with different environmental exposures in rural Malawi. We hypothesized that more adverse environmental exposures would be associated with lower levels of microbiota maturity and diversity. Methods Faecal samples from up to 631 children and mothers participating in a nutrition intervention trial were collected at 1, 6, 12, 18, and 30 months (children) and at 1 month (mothers) after birth and analysed for microbiota composition with 16S rRNA sequencing. Bacterial OTU and genus abundances, measures of microbiota maturity and diversity, and UniFrac distances were compared between participants with different environmental exposures. The exposure variables included socio‐economic status, water source, sanitary facility, domestic animals, maternal characteristics, season, antibiotic use, and delivery mode. Results Measures of microbiota maturity and diversity in children were inversely associated with maternal education at 6, 18, and 30 months and did not otherwise differ consistently between participants with different environmental exposures. Phylogenetic distance was related to season of stool sample collection at all time points. At the level of individual OTUs and genera, season of stool sample collection, type of water source, and maternal education showed most associations with child gut microbiota, while HIV status was the most important predictor of relative OTU and genus abundances in mothers. Conclusion The results do not support the hypothesis that adverse environmental exposures are broadly associated with lower microbiota maturity and diversity but suggest that environmental exposures influence the abundance of several bacterial OTUs and genera and that low maternal education is associated with higher microbiota maturity and diversity.